2022
DOI: 10.3390/nu14030702
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Complementary Feeding, Growth, and Risk of Non-Communicable Diseases: Systematic Review and Meta-Analysis

Abstract: No consensus currently exists on the appropriate age for the introduction of complementary feeding (CF). In this paper, a systematic review is conducted that investigates the effects of starting CF in breastfed and formula-fed infants at 4, 4–6, or 6 months of age (i) on growth at 12 months of age, (ii) on the development of overweight/obesity at 3–6 years of age, (iii) on iron status, and (iv) on the risk of developing (later in life) type 2 diabetes mellitus (DM2) and hypertension. An extensive literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…The fact that a longer duration of breastfeeding has been related to lower rates of obesity in adulthood (29,30), probably makes it necessary to debate not only the time of maternity leave in our environment, in the public and private sectors, but also the idea that teleworking can be an easy tool for facilitating its increasing. In our survey, paediatricians did not detected an early introduction of complementary feeding, a situation that in healthy infants under 6 months does not seem to provide any benefit in developed countries (31).…”
Section: Discussioncontrasting
confidence: 58%
“…The fact that a longer duration of breastfeeding has been related to lower rates of obesity in adulthood (29,30), probably makes it necessary to debate not only the time of maternity leave in our environment, in the public and private sectors, but also the idea that teleworking can be an easy tool for facilitating its increasing. In our survey, paediatricians did not detected an early introduction of complementary feeding, a situation that in healthy infants under 6 months does not seem to provide any benefit in developed countries (31).…”
Section: Discussioncontrasting
confidence: 58%
“…It cannot be forgotten that any attitude that might encourage the early abandonment of breast milk without nutritional benefit, deprives the infant of a number of functional nutrients that are useful, if or even necessary, for an optimal psychophysical development. In addition, the reduction of breastfeeding reduces its protective effect against breast cancer for the mother [19]. Unfortunately, these two aspects of outstanding ethical importance have not been stressed enough in the EFSA statement, when it says "the fact that an infant may be ready from a neurodevelopmental point of view to progress from a liquid to a more diversified diet before six months of age does not imply that there is a need to introduce CFs" [19].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the introduction of complementary food at 4 or 6 months does not influence growth at 12 months of life or on the percentage of obesity at 3 and 6 years. Therefore, introducing complementary foods before the age of 6 months in healthy-term infants does not present any beneficial effect, determining, on the contrary, a reduction in human milk feeding [ 43 ].…”
Section: Resultsmentioning
confidence: 99%